Parameter optimization of smooth blasting with slotted charges in Underground Roadways under high In-Situ Stresses - Niu, Yike; Wang, Jianguo; Zhao, Yanwei; Xu, Wankui; Li, Jinhua; Wang, Mian (Engineering fracture mechanics, 2025)
•Proposes an optimization method for smooth blasting parameters based on slotted charges.•Simulated smooth blasting using slotted charges through numerical simulation.•Reveals the adaptability of the directional fracture mechanism in slotted charges under high in-situ stress conditions. To address the problems of poor tunnel contour formation and severe surrounding rock damage in high in-situ stress environments, this paper proposes an optimization method for smooth blasting parameters based on slotted charges, specifically applied to the −20 m level of the Dahongshan Copper Mine under high stress.Combining theory, simulation, and field tests studies demonstrate that employing slotted charges effectively reduces surrounding rock damage, with the directional energy-concentrating effect significantly diminishing energy transfer in non-slotted directions, reducing rock damage depth.The application of slotted charges has reduced the single-hole charge quantity to 900 g, increased the spacing of the light blastholes from the original 0.4–0.5 m to 0.6 m, increased the thickness of the light blasting layer to 0.6–0.7 m,the half-hole ratio has increased significantly, made the over-excavation rate approach zero, significantly improved the contour smoothness after blasting, and made the fragmentation size of the rock and ore more uniform. This study elucidates the adaptability of the directional rock-breaking mechanism of slotted charges to high in-situ stress, providing theoretical support for blasting energy control and process parameter optimization.